Contrastive analysis of errors analysis in the use of Japanese and Sundanese speech level categories for themselves (Kenjougo and Lemes Keur Sorangan) - Suherman, Eman (Japanese Research on Linguistics, Literature, and Culture, 2022)
This study aims to describe some of the errors in the use of Japanese speech levels in the Kenjougo form by Japanese language learners and the smooth form of Sundanese language for themselves by some Sundanese people. What kinds of errors are found in the use of the two languages, the answers will be presented in this study.The data in this study for the use of the Japanese language were obtained from questionnaires addressed to students of the Japanese Literature Study Program, Faculty of Humanities, Gadjah Mada University semester III, V, and VII. While the data for the use of the Sundanese language consisted of two groups, the first group was obtained from the distribution of questionnaires addressed to Japanese language lecturers who spoke Sundanese and the second group was obtained from housewives, civil servants, retired civil servants, and others. It was concluded that the errors in using Kenjougo in the third semester were 36.36%, the fifth semester errors were 21.27%, and the seventh semester errors were 33.33%. Meanwhile, errors in the use of the lemes keur sorangan form among Japanese language lecturers who speak Sundanese as much as 22% and the public as much as 15%.